Konstruksi Sosial dalam Tradisi Pembacaan Asma’ul Husna dan Wirid Hizib Bahar di Rumah Tahfidz Syeikh Mahmuddin Kota Samarinda: - - Yuliati, Putri; Hudriansyah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This study will first focus on how to read Asma'ul Husna and Wirid HizibBahar. Second, how the congregation interprets the meaning of reading Asma'ulHusna and Wirid Hizib Bahar, Third, how to maintain these rules according to theQur'an. Data analysis of this writing uses data analysis according to Miles andHuberman, the author collects some data obtained from interviews with severaladministrators, teachers and santriwati. This Living Qur'an study uses fieldresearch, which is research that comes from interviews, observation, anddocumentation. Interview sources include Mudir Ma'had, the founder of TahfidzHouse, teachers and administrators of Tahfidz House, jama'ah Santriwati orAsma'ul Husna. The results of this study indicate that the habituation of readingAsma'ul Husna and Wirid Hizib Bahar has become a social activity amongsantriwati of Sheikh Mahmuddin Tahfidz House. The reading of Asma'ul Husnaand Wirid Hizib Bahar is carried out in the hall of the Tahfidz Syeikh MahmuddinHouse in congregation after performing the Asr prayer in congregation.Theprocedure for carrying out the reading of Asma'ul Husna and Wirid Hizib Bahar,namely: Reading Asma'ul Husna 1x, Reading Istighfar 3x, Reading Syahadat 1x,Reading Tawassul, then proceed to read Wirid Hizib Bahar. Textual interpretationAccording to the leader of the Tahfiz House that in Wirid Hizib Bahar there isSurah Al-Ahzab verses 11-12 which are verses so that all desires are immediatelygranted, Surah Maryam verse 1 is a surah that tells about Maryam, the hope isthat by practicing this verse we become servants who are istiqomah in the wayof Allah who are ready to keep away from all evil and everything that Allah forbids,Surah Yaasin verses 1-9 which is the heart of the Qur'an Al-Karim, Surah Thohaverse 111 which contains al-ismul adzhom which if you pray with it, God willing,all wishes will be granted, Surah An-naml verse 1 which is a verse that hasfadhilah in the form of pleasure, Surah Ar-Rahman verses 19-20 are verses aboutlove for God and his creatures. Textual interpretation According to the leader ofthe Tahfiz House that in Wirid Hizib Bahar there is Surah Al-Ahzab verses 11-12which are verses so that all desires are immediately granted, Surah Maryamverse 1 is a surah that tells about Maryam, the hope is that by practicing thisverse we become servants who are istiqomah in the way of Allah who are readyto keep away from all evil and everything that Allah forbids, Surah Yaasin verses1-9 which is the heart of the Qur'an Al-Karim, Surah Thoha verse 111 whichcontains al-ismul adzhom which if you pray with it, God willing, all wishes will begranted, Surah An-naml verse 1 which is a verse that has fadhilah in the form ofpleasure, Surah Ar-Rahman verses 19-20 are verses about love for God and hiscreatures.